2020
DOI: 10.1002/agj2.20072
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous jasmonic acid and humic acid increased salinity tolerance of sorghum

Abstract: Salinity limits germination and plant growth and development in 45 million ha worldwide. Techniques to overcome this problem are needed. This project investigated the effects of jasmonic acid (JA) (0, 5, and 10 mM JA) and humic acid (HA) (0, 3, and 6 g HA kg −1 soil) on growth and physiological parameters of forage sorghum (Sorghum bicolor L. Moench) under different NaCl salinity levels (0, 100, and 200 mM NaCl, with an equivalent electrical conductivity (EC) of 0.12 dSm −1 as control treatment, 3.22, and 5.78… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 52 publications
5
37
1
Order By: Relevance
“…For instance, Alsahli et al [ 179 ] found that a 2-fold increase in SOD, CAT, and APX activity decreased 3-fold H 2 O 2 in salt-stressed wheat by salicylic acid (SA) application compared with untreated control plants. Similarly, the combined application of jasmonic acid (JA) and humic acid also increased APX activity, resulting in salinity tolerance in sorghum [ 180 ], while exogenous application of polyamines regulated sour orange antioxidant responses under salinity stress conditions [ 181 ]. Nitrogen supplementation is also reported to increase the antioxidant (SOD, CAT, APX, GR, MDHAR, DHAR activities and the biosynthesis of AsA and GSH) levels with declining 2.5-fold H 2 O 2 and 1.7-fold O 2 •− generation in wheat under 100 mM NaCl stress [ 182 ].…”
Section: Antioxidant Defense In Plants Under Abiotic Stress: Recenmentioning
confidence: 99%
“…For instance, Alsahli et al [ 179 ] found that a 2-fold increase in SOD, CAT, and APX activity decreased 3-fold H 2 O 2 in salt-stressed wheat by salicylic acid (SA) application compared with untreated control plants. Similarly, the combined application of jasmonic acid (JA) and humic acid also increased APX activity, resulting in salinity tolerance in sorghum [ 180 ], while exogenous application of polyamines regulated sour orange antioxidant responses under salinity stress conditions [ 181 ]. Nitrogen supplementation is also reported to increase the antioxidant (SOD, CAT, APX, GR, MDHAR, DHAR activities and the biosynthesis of AsA and GSH) levels with declining 2.5-fold H 2 O 2 and 1.7-fold O 2 •− generation in wheat under 100 mM NaCl stress [ 182 ].…”
Section: Antioxidant Defense In Plants Under Abiotic Stress: Recenmentioning
confidence: 99%
“…Plant secondary metabolism produces a large number of specialized compounds that do not directly aid in the growth and development of plants but are required for the plant to survive in its environment and under biotic and abiotic stress. Salinity and drought are the most frequent stresses studied in fields and under greenhouse conditions (Ali et al, 2020). Several reports have been published on the impact of HS on the growth of pepper, common beans, rice, tomato, corn, sorghum, and cucumber under these stress conditions (Demir et al, 1999;García et al, 2012;Berbara and García, 2014;Rose et al, 2014;Prado et al, 2016;Van Oosten et al, 2017;Bulgari et al, 2019;Pinos et al, 2019;Ali et al, 2020).…”
Section: Key Benefits Of Hs On Plant Growthmentioning
confidence: 99%
“…Several reports have been published on the impact of HS on the growth of pepper, common beans, rice, tomato, corn, sorghum, and cucumber under these stress conditions (Demir et al, 1999;García et al, 2012;Berbara and García, 2014;Rose et al, 2014;Prado et al, 2016;Van Oosten et al, 2017;Bulgari et al, 2019;Pinos et al, 2019;Ali et al, 2020). One of the underlying mechanisms of the impact of the HS is the interaction with auxin, jasmonic acid and abscisic acid by phytohormonal regulation in the root, which are well-known plant hormones for the stress of drought and salinity (De Hita et al, 2019;Ali et al, 2020). Another example is the synthesis of flavonoids, which are involved in the interception of ultraviolet (UV) as an adaptive mechanism preventing UV in plant physiology (Hollósy, 2002).…”
Section: Key Benefits Of Hs On Plant Growthmentioning
confidence: 99%
“…Salinity stress can significantly inhibit germination and seedling growth, decrease many physiological processes and ultimately reduce crop productivity by causing osmotic stress and/or toxicity of ions as well as by reducing the uptake of important ions such as calcium and potassium 6 . Crop plants can suffer from salinity stress at all growth stages, but germination and early plant stage are known to be more sensitive for most plant species 7 , 8 . Salinity stress affect all growth stages, but germination and early seedling stage are known to be more sensitive to salinity, causing significantly inhibited germination and seedling growth and ultimately decreased crop productivity through osmotic stress and ion toxicity such as Na + and Cl − , as well as throught reduced absorption of important nutrients such as Ca +2 and K + 6 , 9 .…”
Section: Introductionmentioning
confidence: 99%